Methodological Innovation to Increase the Utility and Efficiency of Psychotherapy Research for Patients with Co-occurring Mental Health and Substance Use Disorders - Hien, Denise A. (2009)
Psychotherapy research with chronic and difficult-to-treat populations such as those with co-occurring mental health and addictive disorders can employ flexible research designs, which allow for a systematic, yet non-linear relationship between efficacy and effectiveness designs. Outcomes research can bypass the efficacy-effectiveness dichotomy through use of a hybrid model (Carroll & Rounsaville, 2003) conducted in the context of community treatment settings in collaboration with community providers. We present the case for using this methodological approach as a means of advancing psychotherapy research and practice, while translating and disseminating empirically supported treatments with more efficiency. A hybrid model study conducted within the National Institute on Drug Abuse’s Clinical Trials Network illustrates the application. These findings inform new directions for future research.